Histopathological evaluation of the platelets rich fibrin and bone marrow on healing of experimental induced distal radial fracture in local dogs: 1Thanoon M.G., 2 M. J. Eesa and 3Alkenanny E.R. - G., Thanoon M. (The Iraqi Journal of Veterinary Medicine, 2022)
The aim of this study was to evaluate the effects of platelets rich fibrin and bone marrow on healing of distal radial fracture in local dogs. Twenty four adult animals (males and non-pregnant females of local breed dogs); had mean age 2.6 ±0.15 years and body weight 24.58 ±1.07 kgs were used. The experimental animals were randomly divided into three equal groups. First group (Control group), transverse fracture was induced at the distal portion of radial bone and immobilized by using Plaster of Paris, the fracture line didn’t treated with any substance. Second group (Platelets Rich Fibrin group), in which the fracture line was surrounded by the platelets rich fibrin. Third group (Bone Marrow group) in which the fracture line was surrounded by autologous bone marrow. The histopathological results confirmed that the third group was the best one in its response for fractured bone healing in both periods sixth and tenth week, while the second group was came in the second rank, whereas the first group was the slowest response for fractured bone healing, represented by trabecular bone formation. The concentration rates of calcium and alkaline phosphatase enzyme increased at the weeks that follow surgical operation. In conclusion, the using of bone marrow and platelets rich fibrin are enhance the healing of distal radial fracture.